- 1-214-256-5804
- info@tutorpace.com

Solution: Given is the equation 3x/(x + 2) - 1 = 5/(x+2).

Here the left had side has the equation 3x/(x + 2) - 1.

Take the common denominator that will be (x + 2)

3 x /(x + 2) - (x + 2) / (x + 2) = (3 x - x - 2)/(x+2) = (2 x - 2)/ (x + 2).

This gives: (2 x - 2)/ (x + 2)

The denominator on both sides is (x + 2) equating the numerators.

This gives: 2 x - 2 = 5.

Add 2 on both sides.

This gives 2 x = 7.

Divide both sides of the equation by 2.

Therefore. x = 7/2.

Solution: Given is the equation 6x/(x + 10) = 1.

Multiply both sides of the equation by x+10.

This give 6x = x+ 10.

Subtracting both sides of the equation by x. 5x = 10.

Divide both sides of the equation by 5.

Therefore. x = 2.